2021
DOI: 10.1142/s0192415x21500610
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Cross-Sectional Studies on Traditional Chinese Medicine

Abstract: Cross-sectional studies on traditional Chinese medicine (TCM-CSs) have become the most published type of TCM observational study; however, the research scope of current TCM-CSs is unknown. A scoping review of the literature was performed. A descriptive approach to summarize the core study characteristics was prepared, along with structured tables and figures to identify salient points of similarities and differences noted across studies. The reporting quality of TCM-CSs was assessed according to the Strengthen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In the comparison of different subgroups, we found that the reporting quality in Chinese Dissertations was better than those in journal publications regarding the ITCWM specifics. This could be attributed to the page and words limitations for Chinese journal publications [ 48 ]. Additionally, as the Dissertation is the basis for scholars to obtain their degree, higher requirements of quality were included.…”
Section: Discussionmentioning
confidence: 99%
“…In the comparison of different subgroups, we found that the reporting quality in Chinese Dissertations was better than those in journal publications regarding the ITCWM specifics. This could be attributed to the page and words limitations for Chinese journal publications [ 48 ]. Additionally, as the Dissertation is the basis for scholars to obtain their degree, higher requirements of quality were included.…”
Section: Discussionmentioning
confidence: 99%
“…16 Similar previous studies investigated the situation of TCM use in a certain population. 17 Even though those studies had a large sample size or a long duration of follow-up, a lack of sufficient information 18,19 and large heterogeneity 20,21 were found between these studies. Our population consisted of only breast cancer cases, whereby providing an excellent degree of consistency.…”
Section: Discussionmentioning
confidence: 99%